An update on the safety of treating relapsing-remitting multiple sclerosis. Issue 10 (3rd October 2019) - Chisari, Clara G.; Toscano, Simona; D'Amico, Emanuele; Lo Fermo, Salvatore; Zanghì, Aurora; Arena, Sebastiano; Zappia, Mario; Patti, Francesco
ABSTRACT: Introduction : In the last 20 years the armamentarium for multiple sclerosis (MS) treatment has been enriched from an increasingly wider variety of new drugs in order to reach a better control of the disease with a better patient compliance. Areas covered : With this great variety of therapeutic options, physicians may face new and major challenges. The huge amount of data from pilot studies and real-life settings showed that the first-line therapies have a better safety profile. On the other hand, the risks associated with newer drugs, with more selective mechanism of action and targeting specific pathways of MS pathophysiology, are not yet fully established. In particular, real-life use of these advanced drugs has raised important safety issues as long-term effects and potential risks are not yet known and remain to be carefully evaluated. Expert opinion : No time like the present, the physician faces new and major challenges in order to choose the best available therapy for MS. With the increasing number of drugs for treating MS and the lack of safety data, observational studies and post-marketing surveillance activities are crucial in order to improve the knowledge about the safety profile of these drugs and the therapeutic management in clinical practice settings.